HAKIKAT DAN SISTEM NILAI DALAM KONTEKS PENDIDIKAN (Sistem Nilai: Keluarga, Masyarakat, Kebudayaan dan Agama) - Toriqularif, Muhammad (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2017)
The lofty values that serve as guidelines for human life is a necessity for anyone who desires a happy life of worldly and hereafter good someone as an individual or part of a system. Man cannot live alone, hence each individual wherever possible can mingle with other individuals. Human Keberbauran in a particular community did not escape with the existence of rules and norms that apply as well as an accompanying value. This is the value of the existence of a person can be said to be good or is deemed otherwise. To understand the meaning of a value it then very determined educational role. Keywords: Nature, Value System, Education